Study of a roadmap for carbon capture and storage development in Guangdong Province, China. Issue 9 (20th October 2016) - Huang, Ying; Guo, Hongxu; Liao, Cuiping; Zhao, Daiqing; Zhou, Di; Liu, Qiang; Li, Xiaochun; Liang, Xi; Li, Jia
Abstract : Energy consumption and greenhouse gas emissions are increasing rapidly in Guangdong, an economically developed Chinese province. Carbon capture and storage (CCS) is an important approach to lower carbon concentration in this area. This study provides guidance and recommendations for CCS development and demonstration by analysing the necessity of CCS in Guangdong. Furthermore, this study identifies the major opportunities and technical demands related to CCS development in this province based on a sectoral analysis of emission inventory and the forecasting and identification of the potential CO2 storage capacity. A CCS development roadmap is then developed for Guangdong based on the analysis results, and the milestone goals of this roadmap from the present until 2030 are presented in accordance with the development of technology in and the current status of Guangdong. In addition, the roadmap suggests CCS support policies.